2017
DOI: 10.1038/s41598-017-06471-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ginsenoside Rb1 and Rd protects the retina against bright light-induced degeneration

Abstract: Photoreceptor degeneration is a central pathology of various retinal degenerative diseases which currently lack effective therapies. Antioxidant and anti-inflammatory activities are noted for Panax notoginsenoside saponins (PNS) and related saponin compound(s). However, the photoreceptor protective potentials of PNS or related saponin compound(s) remain unknown. The current study revealed that PNS protected against photoreceptor loss in bright light-exposed BALB/c mice. Combination of ginsenoside Rb1 and Rd, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…The internal genetic factors and external environmental factors determine the quality of medicinal materials. Ginseng saponin, the main active ingredient of ginseng, has many pharmacological and immunological activities [31,32,33]. Ginseng modestly yet significantly improves fasting blood glucose in people with and without diabetes [34], and a study by Lin et al showed that ginseng also enhances cardiac contractility in other animal species [35].…”
Section: Discussionmentioning
confidence: 99%
“…The internal genetic factors and external environmental factors determine the quality of medicinal materials. Ginseng saponin, the main active ingredient of ginseng, has many pharmacological and immunological activities [31,32,33]. Ginseng modestly yet significantly improves fasting blood glucose in people with and without diabetes [34], and a study by Lin et al showed that ginseng also enhances cardiac contractility in other animal species [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the effect of miR-155 on retinal apoptosis and angiogenesis predominantly in cell culture and murine models that resemble retinopathy of prematurity (ROP) or age-related macular degeneration (AMD) (15, 17, 39, 40, 41). In this scenario, overexpression of miR-155 in the retina seemed to be detrimental (15, 17, 39). In contrast, the levels of endogenous miR-155 were decreased in retinal pigment epithelium/choroidal tissues after laser photocoagulation in mice.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Our previous study has also shown that Rb1 decreases the expression of miR-155 in lipopolysaccharide (LPS)-stimulated macrophages. 14 However, it is unknown whether Rb1 is effective at counteracting the pro-hypertrophic effect of Ang II. Meanwhile, whether Rb1 suppresses cardiac hypertrophy-associated inflammation remains to be addressed.…”
Section: Introductionmentioning
confidence: 99%